Detection of novel Plasmodium falciparum coronin gene mutations in a recrudescent ACT-treated patient in South-Western Nigeria - Ajibaye, Olusola; Olukosi, Yetunde Adeola; Oriero, Eniyou C.; Oboh, Mary Aigbiremo; Iwalokun, Bamidele; Nwankwo, Ikechukwu Chidiebere; Nnam, Chinaza Favour; Adaramoye, Olawunmi Victoria; Chukwemeka, Somadina; Okanazu, Judith; Gabriel, Eniafe; Balogun, Emmanuel Oluwadare; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Routine surveillance for antimalarial drug resistance is critical to sustaining the efficacy of artemisinin-based Combination Therapies (ACTs). Plasmodium falciparum and non-Pfkelch-13 artemisinin (ART) resistance-associated mutations are uncommon in Africa.We investigated polymorphisms in Plasmodium falciparum actin-binding protein (Pfcoronin) associated with in vivo reduced sensitivity to ART in Nigeria.Fifty-two P. falciparum malaria subjects who meet the inclusion criteria were followed up in a 28day therapeutic efficacy study for artemether-lumefantrine in Lagos, Nigeria. Parasite detection was done by microscopy and molecular diagnostic approaches involving PCR amplification of genes for Pf18S rRNA, varATS, telomere-associated repetitive elements-2 (TARE-2). Pfcoronin and Pfkelch-13 genes were sequenced bi-directionally while clonality of infections was determined using 12 neutral P. falciparum microsatellite loci and msp2 analyses. Antimalarial drugs Genetic analysis of this isolate identified two new Pfcoronin SNVs (I68G and L173F) in addition to the P76S earlier reported. Linkage-Disequilibrium as a standardized association index, IA S , between multiple P. falciparum loci revealed significant LD (IA S = 0.2865, P=0.02, Monte-Carlo simulation) around the neutral microsatellite loci. The pfdhfr/pfdhps/pfmdr1 drug resistanceassociated haplotypes combinations, (108T/N/51I /164L/59R/581G/86Y/184F), were observed in two samples.Pfcoronin mutations identified in this study, with potential to impact parasite clearance, may guide investigations on emerging ART tolerance in Nigeria, and West African endemic countries.